Science and inquiry-based teaching and learning: a systematic review - Urdanivia Alarcon, Diego Antonio; Talavera-Mendoza, Fabiola; Rucano Paucar, Fabian Hugo; Cayani Caceres, Karina Sandra; Machaca Viza, Rina (Frontiers in Education, 2023)
The use of the inquiry-based instructional approach allows the development of research skills and construction of scientific knowledge. When coupled with effective teaching strategies, this approach allows for the modeling of the world's laws and theories with reality, thereby making science more accessible. The objective is to analyze the instructional models, subject areas, and developmental areas implemented by secondary school teachers in science education. After a systematic review of Web of Science, Scopus, and ERIC databases from 2013 to 2022, 51 articles were selected, which include qualitative, experimental, and descriptive works. The results indicate that teaching science has a tendency to achieve learning using scientific reasoning, with high expectations based on evidence, and a predisposition to the use of constructivism instructional models. The need for continuous teacher training to understand scientific knowledge and to master strategies for implementing open inquiry is emphasized. It is concluded that all studies focus on IBL, which encourages new ways of conducting science while considering the cyclic application processes. Similarly, the trend toward technology-based serious games, such as video, audio, and digital platforms, is becoming increasingly evident in current education, as is the drive to develop STEM methodologies.